2013
DOI: 10.1080/13504622.2013.843646
|View full text |Cite
|
Sign up to set email alerts
|

The effect of visitor motivation on the success of environmental education at the Toronto Zoo

Abstract: With the number and scope of environmental challenges continuing to increase, an understanding of the effectiveness of conservation programs is essential in order to allocate limited resources. This paper examines the effectiveness of environmental education within a zoo setting, focusing on the role of learners' identity-related motivation. Results from survey (n = 296) and interview (n = 116) data collected from visitors to the Toronto Zoo suggest that education success is dependent on visitors' dominant mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
3
9
0
1
Order By: Relevance
“…The pathways to learning also reflected some similarities between the visitors (Section 5.4.2). For all respondents, motivations influenced the experience during the visit and subsequent learning, a finding in common with previous research Falk et al, 1998;Falk, 2006;Packer & Ballantyne, 2002;Schultz & Joordens, 2014).…”
Section: Similarities Between Visitors From Different Cultural Backgrsupporting
confidence: 84%
See 2 more Smart Citations
“…The pathways to learning also reflected some similarities between the visitors (Section 5.4.2). For all respondents, motivations influenced the experience during the visit and subsequent learning, a finding in common with previous research Falk et al, 1998;Falk, 2006;Packer & Ballantyne, 2002;Schultz & Joordens, 2014).…”
Section: Similarities Between Visitors From Different Cultural Backgrsupporting
confidence: 84%
“…While previous research has shown that conservation messages are an important component of a wildlife tourism experience , the effectiveness of conservation messages in interpretation has received little attention (Moscardo, 2014). More than half of the visitors in this study did not recall a single conservation message, a finding in common with previous research (Schultz & Joordens, 2014). This suggests that visitors may find it difficult to clearly articulate their conservation learning.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…While it is small compared to our knowledge of American landowners and their ESA , this literature does suggest that private stewardship is occurring but landowners are often unaware of policy and listed species. Other literature has examined the role of zoos, namely the Toronto Zoo, in the conservation of wildlife and species at risk (Schultz and Joordens ; Olive and Jansen ). Zoos act as research centres but also oversee captive breeding programs where species, such as the endangered Blanding turtle, are reintroduced into the wild.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have explored visitor perspectives regarding donation requests or their impact on visitor satisfaction or behavior, with some visitors perceiving donations as a way of being included in zoo conservation efforts, while others seem uncomfortable with being asked for money (Smith et al, , ). Furthermore, not all zoo visitors may recognize donation as a potential conservation action (Schultz & Joordens, ), resulting in no donations being given when such opportunities arise (Smith & Broad, ). Since financial support potentially increases the impact of zoo‐based conservation projects (Gusset & Dick, ), there is a critical need to investigate donation requests within the zoo context.…”
Section: Introductionmentioning
confidence: 99%